Organ-Specific Therapeutic Effect of Paclitaxel and Carboplatin Chemotherapy After Platinum-Based Chemotherapy and Pembrolizumab for Metastatic Urothelial Carcinoma - Furubayashi N (Research and Reports in Urology, 2020)
Nobuki Furubayashi, Takahito Negishi, Akihiro Miura, Nobutaka Nakamura, Motonobu Nakamura Department of Urology, National Hospital Organization Kyushu Cancer Center, Fukuoka, JapanCorrespondence: Nobuki Furubayashi Tel +81-92-541-3231Fax +81-92-551-4585Email furubayashi-jua@umin.ac.jpBackground: To evaluate the organ-specific therapeutic effect of paclitaxel and carboplatin (TC) chemotherapy in patients who failed platinum-based chemotherapy and pembrolizumab for metastatic urothelial carcinoma (UC).Patients and Methods: We retrospectively reviewed the data of patients with metastatic UC who had received TC chemotherapy after the failure of platinum-based chemotherapy and pembrolizumab. The RECIST 1.1 criteria were used to assess the objective response to pembrolizumab and TC chemotherapy at tumor sites.Results: We analyzed 8 patients (male, n=5; female, n=3; median age, 65 years old). All patients except one had visceral metastasis. The median overall survival for TC was 10.9 months (95% confidence interval, 1.0‑12.7 months), and the objective response rate was 25.0% (partial response [PR]: 2 cases). The metastatic organs were the lymph nodes in 5 cases (number of tumor sites: 8), lung in 4 cases (number of tumor sites: 12), liver in 3 cases (number of tumor sites: 14), bone in 3 cases (number of tumor sites: 12), and primary lesion in 3 cases (number of tumor sites: 3). There were no cases of a complete response or progressive disease in any metastatic organs due to TC chemotherapy. A PR was seen in 2 cases of lymph node metastasis (40.0%), 2 cases of lung metastasis (50.0%), and 2 cases of liver metastasis (66.7%). All 3 cases of bone metastasis showed stable disease, as did all 3 cases of primary lesion. Improvement in the therapeutic effect of TC chemotherapy compared with pembrolizumab was observed in 2 cases (40.0%) of lymph node metastasis, 2 cases (50.0%) of lung metastasis, and 1 case (33.3%) of liver metastasis.Conclusion: Lymph node, lung, and liver metastases may respond to TC chemotherapy, even if exacerbated with pembrolizumab after platinum-based chemotherapy in metastatic UC.Keywords: urothelial carcinoma, platinum-based chemotherapy, pembrolizumab, paclitaxel, carboplatin, organ-specific therapeutic effect